The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0883073819834430
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Age Modifies Subjective Visual Function After Cerebral Hemispherectomy

Abstract: Background: Cerebral hemispherectomy is typically used to treat patients with pharmacoresistant epilepsy. Visual-related outcomes are relatively unstudied in this population, aside from the knowledge that patients develop a complete homonymous hemianopia contralateral to the side of the hemispherectomy. The purpose of this study was to determine and characterize parent-reported functional visual, oculomotor, and postural changes in a large population of patients following cerebral hemispherectomy. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These symptoms occurred more frequently in dominant hemisphere involvement. Postoperative visual field and/or visual acuity worsening has been demonstrated in pediatric series ( Chen et al, 2019 ; Meer et al, 2021 ). Chen et al (2019) reported that 49 % of their pediatric cases developed de novo or had worsening of their preoperative strabismus.…”
Section: Complications: An Overview and A Consensus On Their Avoidancementioning
confidence: 99%
See 2 more Smart Citations
“…These symptoms occurred more frequently in dominant hemisphere involvement. Postoperative visual field and/or visual acuity worsening has been demonstrated in pediatric series ( Chen et al, 2019 ; Meer et al, 2021 ). Chen et al (2019) reported that 49 % of their pediatric cases developed de novo or had worsening of their preoperative strabismus.…”
Section: Complications: An Overview and A Consensus On Their Avoidancementioning
confidence: 99%
“…Postoperative visual field and/or visual acuity worsening has been demonstrated in pediatric series ( Chen et al, 2019 ; Meer et al, 2021 ). Chen et al (2019) reported that 49 % of their pediatric cases developed de novo or had worsening of their preoperative strabismus. It is of interest, that the vast majority of these patients developed torticollis from compensating for their visual deficits ( Chen et al, 2019 ).…”
Section: Complications: An Overview and A Consensus On Their Avoidancementioning
confidence: 99%
See 1 more Smart Citation